The Democracy – Economic Growth Nexus: A Systematic Literature Review - Yangailo, Tryson (Brawijaya Journal of Social Science, 2024)
The purpose of this study was to present a systematic literature review on the relationship between democracy and economic growth. The goal was to provide scholars and policymakers with important new information on how democracy affects economic growth, as well as solid evidence of the gaps in the literature that need to be filled immediately. The research used a methodological analysis of the literature found in two databases, Google Scholar and Semantic Scholar.The study presents that majority of the studies reviewed show that democracy has a long-term, substantial positive impact on a country's economic growth. But democracy alone cannot promote economic expansion, especially in developing countries. Democracies can promote economic growth in a variety of ways, but how well these efforts work depends on the quality of democratic institutions, the legal system and broader socio-economic conditions. According to the study, elected governments should implement laws and procedures that protect and promote democracy while addressing the needs of the population in order to achieve sustainable economic growth.